2020
DOI: 10.1002/ijc.33436
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the lifetime brain/central nervous system cancer risk associated with childhood head CT scanning in Japan

Abstract: The use of computed tomography (CT) scanning has increased worldwide over the decades, and Japan is one of the leading countries in annual frequency of diagnostic CT. Although benefits of CT scan are undisputable, concerns have been raised about potential health effects of ionizing radiation exposure from CT, particularly among children who are likely more susceptible to radiation than adults. Our study aims to evaluate the cumulated lifetime risk of the brain/central nervous system (CNS) cancer due to head CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A study to evaluate the Lifetime attributable cancer risk related to prevalent CT scan procedures in pediatric medical imaging centers [23] showed a LAR following a chest CT scan of 68.23 per 100,000 FOR patients Of <1-year-old and abdomen-pelvic CT scans of 57.30 per 100,000 for patients within the age group 10-to 15-years. The values obtained from their study [23] were higher than that obtained from the study by Semghoul et al [22], Kadowak et al [24] and the index study. Although the model and number of CT scanner slices used in their study [23] could not be ascertain, the fact that the study population was only children (pediatric) could have contributed to the variations observed [25,26,27].…”
Section: Discussioncontrasting
confidence: 55%
“…A study to evaluate the Lifetime attributable cancer risk related to prevalent CT scan procedures in pediatric medical imaging centers [23] showed a LAR following a chest CT scan of 68.23 per 100,000 FOR patients Of <1-year-old and abdomen-pelvic CT scans of 57.30 per 100,000 for patients within the age group 10-to 15-years. The values obtained from their study [23] were higher than that obtained from the study by Semghoul et al [22], Kadowak et al [24] and the index study. Although the model and number of CT scanner slices used in their study [23] could not be ascertain, the fact that the study population was only children (pediatric) could have contributed to the variations observed [25,26,27].…”
Section: Discussioncontrasting
confidence: 55%
“…In Japan, an epidemiological study on the risk of brain tumors showed that neither whole-head CT nor the cumulative brain dose increased the risk of glioma or all brain tumors [28]. By contrast, cancer risk calculation using LSS risk models indicated that a small but non-negligible portion of CNS cancer cases might be attributable to head CT examinations in children, while the annual frequency of childhood CT examinations decreased over time [4]. However, note that a small but non-negligible portion increase might be detected by epidemiologically observing all the children who underwent CT examinations in Japan.…”
Section: Discussionmentioning
confidence: 98%
“…If the practice is justified, the International Commission on Radiological Protection (ICRP) recommends that optimization should be performed to reduce the dose [1]. The radiation risk has been quantified using the model calculation based on the epidemiological study of atomic bomb survivors in Hiroshima and Nagasaki [2][3][4]. With the recent increase in CT examinations, however, epidemiological studies on radiation exposure from pediatric CT scans have attracted attention from the viewpoint of radiological protection [5].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to ionizing radiation is associated with the risk of cancer, particularly in children, who tend to be more radiosensitive than adults [1][2][3][4]. Three recent studies from the UK, Netherlands, and Japan have published data supporting the association of CT performed in early childhood with the subsequent real risk of malignancy, which was attributed solely to the CT scan [1,5,6]. Pearce et al [1] reported a positive association between the radiation dose from CT and leukemia [excess relative risk (ERR) per mGy: 0.036, 95% CI: 0.005-0.120] and brain tumors (ERR: 0.023, 95% CI: 0.010-0.049): pediatric CT scans delivering cumulative doses of about 50 mGy may almost triple the risk of leukemia and doses of about 60 mGy may triple the risk of brain cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of brain tumors was higher in the cohort of children who underwent CT scans compared to the general population. Kadowaki et al [6] investigated 138532 head CT examinations performed between the ages of 0 to 10 years. They found that CT consequently induced a lifetime excess of 22 cases (1 per 6300 scans) of brain/CNS cancers, accounting for 5% of the total cases.…”
Section: Introductionmentioning
confidence: 99%